Analysis of Literacy Process of Learning Science in Elementary School: A Case Study in Jepara - Mustakul, Setiyawan; Sumaji; Widjanarko, Mochamad (Asian Journal of Assessment in Teaching and Learning, 2023)
The study aims to examine students’ interest in learning science, categorizing it into high, moderate, and low levels among fourth-grade students at SD Negeri 01 Raguklampitan Batealit Jepara. The purpose is to describe and analyze the literacy process in science learning for these students. The research employs a qualitative case study method involving observations, interviews, and documentation. In elementary education, literacy encompasses the development of skills in writing, reading, arithmetic, speaking, and problem-solving, all of which are essential for everyday life. The subjects of this research include fourth-grade students, their teachers, and the school principal at SD N 01 Raguklampitan. One of the ways to foster literacy is through science education. The findings reveal that students with high interest (subjects 1 and 2) enjoy science lessons, those with moderate interest (subjects 3 and 4) are focused during lessons, and those with low interest (subjects 5 and 6) participate but struggle to understand much of the material.